Young Women, Inherited Capital, and Political Kinship in Indonesia - Safitri Elfandari; Annisa Rahmawati; M. Agung Aimar Billah; Leti Karmila (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
This study examines the role of young women politicians in Indonesia’s political dynasties through the lens of Pierre Bourdieu’s theory of capital. It explores how familial ties, alongside various forms of capital, contribute to their political participation and electoral success. Using a qualitative literature study, this research analyzes various scholarly references to understand how economic, social, cultural, and symbolic capital collectively facilitate access to power. The study focuses on three female politicians: Diah Pikatan Orissa Putri Hapsari, Annisa Desmond Mahesa, and Hillary Brigitta Lasut—who secured legislative positions in the 2024 election. Findings indicate that political kinship serves as one of the key factors in their political trajectory, complementing their accumulated capital in navigating the electoral process. This research highlights how the interplay of inherited capital, particularly economic and social capital, strengthens their positioning within Indonesia’s political landscape while also reflecting broader patterns of power reproduction at regional and national levels.